Correlation Between Pre-Operative Sleep Disturbance and Post-Operative Pain in Patients With Rotator Cuff Tear - Wu, Hui; Su, Wanying; Huang, Shengtao; Xiao, Yili; Lu, Liang (Frontiers in Integrative Neuroscience, 2022)
Objectives: The aim of this study is to investigate the relationship between preoperative sleep disturbance and postoperative pain in patients with rotator cuff tear, and to provide theoretical basis for taking corresponding interventions to alleviate postoperative pain in patients with rotator cuff tear. Methods: 87 patients who had underwent shoulder arthroscopy due to rotator cuff injury in Hunan Provincial People‘s Hospital from January to October 2021 were selected as the research subjects. The Pittsburgh Sleep Quality Index (PSQI) was used to evaluate sleep quality of patients with rotator cuff tear. All patients were divided into low sleep quality group (PSQI score >7 points, n=61) and high sleep quality group (PSQI score ≤7 points, n=26). Postoperative pain was assessed by using the Numerical Rating Scale (NRS). General clinical data of the patients were collected at 1 day, 2 days, and 1 month after surgery. Univariate and multivariate analyses of influencing factors were performed in patients with moderate or above pain at 1 month after surgery. Results: The score of postoperative pain of patients in high sleep quality group was significantly lower than that of patients in low sleep quality group (P<0.05). A total of 35 patients (40.2%) had moderate or above pain at 1 month after surgery, including 5 patients (19.2%) in high sleep quality group and 30 patients (49.2%) in low sleep quality group. The incidence rate of low sleep quality group was significantly higher than that of high sleep quality group (P=0.009). After controlling confounding factors, preoperative sleep disturbance of patients was still independently associated with the occurrence of moderate or above pain at 1 month after surgery (OR=3.794, 95% CI: 1.261-11.409, P=0.018). Conclusion: Preoperative sleep disturbance can increase the risk of postoperative moderate or above pain in patients with rotator cuff tear. Paying more attention to and actively improving preoperative sleep disturbance can effectively promote postoperative pain management in patients with rotator cuff tear.